Four Questions to Guide Decision-Making for Data Sharing and Integration - Hawn Nelson, Amy; Zanti, Sharon (International Journal of Population Data Science, 2023)
Introduction This paper presents a Four Question Framework to guide data integration partners in building a strong governance and legal foundation to support ethical data use. Objectives While this framework was developed based on work in the United States that routinely integrates public data, it is meant to be a simple, digestible tool that can be adapted to any context. Methods The framework was developed through a series of public deliberation workgroups and 15 years of field experience working with a diversity of data integration efforts across the United States. Results The Four Questions - Is this legal? Is this ethical? Is this a good idea? How do we know (and who decides)? - should be considered within an established data governance framework and alongside core partners to determine whether and how to move forward when building an Integrated Data System (IDS) and also at each stage of a specific data project. We discuss these questions in depth, with a particular focus on the role of governance in establishing legal and ethical data use. In addition, we provide example data governance structures from two IDS sites and hypothetical scenarios that illustrate key considerations for the Four Question Framework. Conclusions A robust governance process is essential for determining whether data sharing and integration is legal, ethical, and a good idea within the local context. This process is iterative and as relational as it is technical, which means authentic collaboration across partners should be prioritized at each stage of a data use project. The Four Questions serve as a guide for determining whether to undertake data sharing and integration and should be regularly revisited throughout the life of a project. Highlights Strong data governance has five qualities: it is purpose-, value-, and principle-driven; strategically located; collaborative; iterative; and transparent. Through a series of public deliberation workgroups and 15 years of field experience, we developed a Four Question Framework to determine whether and how to move forward with building an IDS and at each stage of a data sharing and integration project. The Four Questions—Is this legal? Is this ethical? Is this a good idea? How do we know (and who decides)? —should be carefully considered within established data governance processes and among core partners.